Persistence of Antibodies Against Spike Glycoprotein of SARS-CoV-2 in Healthcare Workers Post Double Dose of BBV-152 and AZD1222 Vaccines - Choudhary, Hari Ram; Parai, Debaprasad; Chandra Dash, Girish; Kshatri, Jaya Singh; Mishra, Narayan; Choudhary, Prasanta Kumar; Pattnaik, Dipti; Panigrahi, Kumudini; Behera, Susmita; Ranjan Sahoo, Nihar; Podder, Sreeparna; Mishra, Adyasha; et al. (Frontiers in Medicine, 2021)
Purpose: We investigated the persistence of the vaccine-induced immunoglobulin G (IgG) antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among healthcare workers (HCWs) in Odisha who received a complete dose of either Covaxin or Covishield vaccine. Methods: This 24-week longitudinal cohort study was conducted from January to July 2021 with participants from 6 healthcare and research facilities of Odisha to understand the dynamicity of the vaccine-induced IgG antibodies against SARS-CoV-2 after the complete dose of vaccines. Results: Serum samples were collected from 614 participants during each follow-up and were tested in two chemiluminescent microparticle immunoassay (CLIA)-based platforms to detect SARS-CoV-2 antibodies both qualitatively and quantitatively. Among these participants, 308 (50.2%) participants were Covishield recipients and the rest 306 (49.8%) participants took Covaxin. A total of 81 breakthrough cases were recorded and the rest 533 HCWs without any history of postvaccination infection showed significant antibody waning either from T3 (Covaxin recipient) or T4 (Covishield recipient). The production of vaccine-induced IgG antibodies is significantly higher (p < 0.001) in Covishield compared with Covaxin. Covishield recipients produced higher median anti-S IgG titer than Covaxin. No statistically significant differences in antibody titers were observed based on age, gender, comorbidities, and blood groups. Conclusion: This 6-month follow-up study documents a 2-fold and 4-fold decrease in spike antibody titer among Covishield and Covaxin recipients, respectively. The clinical implications of antibody waning after vaccination are not well understood. It also highlights the need for further data to understand the long-term persistence of vaccine-induced antibody and threshold antibody titer required for protection against reinfection.